2021
DOI: 10.1155/2021/8872139
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Larvicidal Activity of Lavandula angustifolia Subsp. angustifolia and Lavandula dentata Spp. dentata Essential Oils against Culex pipiens Larvae, Vector of West Nile Virus

Abstract: The Culex pipiens mosquito (Diptera: Culicidae) is highly suspected to be the vector responsible for the spread of several parasitic and viral diseases. The use of synthetic insecticides is generally the preferred method of controlling these mosquitoes’ proliferation. However, it has led to resistance problems in target mosquitoes and environmental damage. Hence, diverse plant extracts could be considered as an alternative and potential source as mosquito control agents. In this study, essential oils of Lavand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…These effects were expected owing to the active constituents of these oils. The major components present in lavender essential oil are as determined by GC–MS in this study corresponded with the findings of previous studies ( El-Akhal et al, 2021 , Karamaouna et al, 2013 ), as did the components present in the peppermint essential oil ( Ebadollahi et al, 2017 , Mackled et al, 2019 , Samarasekera et al, 2008 ) and the rosemary essential oil ( Jafari-sales and Pashazadeh, 2020 , Zeghib et al, 2020 ). Generally, the tested three essential oils recorded chemical constituents and their insecticidal activities in accordance with the methods of several previous studies reviewed by Ebadollahi et al (2020) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These effects were expected owing to the active constituents of these oils. The major components present in lavender essential oil are as determined by GC–MS in this study corresponded with the findings of previous studies ( El-Akhal et al, 2021 , Karamaouna et al, 2013 ), as did the components present in the peppermint essential oil ( Ebadollahi et al, 2017 , Mackled et al, 2019 , Samarasekera et al, 2008 ) and the rosemary essential oil ( Jafari-sales and Pashazadeh, 2020 , Zeghib et al, 2020 ). Generally, the tested three essential oils recorded chemical constituents and their insecticidal activities in accordance with the methods of several previous studies reviewed by Ebadollahi et al (2020) .…”
Section: Discussionsupporting
confidence: 91%
“…quinquefasciatus , revealing the potent larvicidal effect of peppermint oil ( Manimaran et al, 2012 ). El-Akhal et al (2021) showed that lavender oil at 800 ppm resulted in 100% larval mortality with an LC 50 of 140 ppm against Cx. pipiens larvae.…”
Section: Discussionmentioning
confidence: 99%
“…pipiensin Egypt [7]. Some of the applied EOs in current study had insecticidal effect against some other dipteran flies;T. foenum and B. compestris [49] and M. chamomilla, P. anisum, R. officinalis [9] were effective agianst Lucilia sericata.A. sativum [11] and L. angustifolia, Cinnamomum camphora, and Allium cepa [10] inducedlarvicidal effect against the oestrid fly, Cephalopina titillator (Clark).…”
Section: Discussionmentioning
confidence: 81%
“…The four monoterpenes evaluated through the binary mixtures in our study constitute the major constituents in many EOs, such as Rosmarinus officinalis, Mentha pulegium, and Lavandula [30][31][32]. Indeed, 1,8-cineol (a monoterpene ether) has been reported to be toxic to many insect species, including C. pipiens [21].…”
Section: Discussionmentioning
confidence: 99%